Analysis of the Influence of Perceived Value on Gen Z's Revisit Intention with Customer Satisfaction as An Intervening Variable at The Museum Bahari Jakarta - Melissa Priskila Saksono; Imam Ardiansyah (Dinasti Publisher, 2024)
The aim of this research is to analyze the influence of perceived value or perceptions related to the values that generation Z has and how to increase this value so that there is satisfaction that creates interest in returning to the Maritime Museum. The research method used is quantitative with questionnaires as a means of data collection. Data was distributed to 100 generation Z respondents who had visited the Jakarta Maritime Museum. The data analysis technique used is path analysis to test the relationship between the variables studied. The research results show that quality value has a significant effect on revisit intention with a p-value of 0.014. Then the quality value on customer satisfaction is significant with a p-value of 0.000. The emotional value of revisit intention is not significant with a p-value of 0.404. Then emotional value on customer satisfaction has a significant effect with a p-value of 0.000. The price value on revisit intention is also significant with a p-value of 0.029 and the price value on customer satisfaction is also significant with a p-value of 0.005. The latest results also show that customer satisfaction is significant on revisit intention with a p-value of 0.000. Based on the results of this research, it can be concluded that by increasing values such as quality, emotional and price, it will have an impact on the satisfaction that visitors feel, and if this satisfaction is in line with their expectations then there will be an interest in visiting again from generation Z. Museum Bahari Jakarta needs to focus on developing service quality, as well as presenting information that is not only educational but also interesting, as well as modernization efforts by combining digital elements in museum collections and exhibitions.